ANALISIS KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK MTsN SABANG MELALUI IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING - Nafisah Hanim (Lantanida Journal, 2019)
This Research to analyze the abilityof students through the implementation of the Discovery Learning learning model has been carried out at MTsN Sabang. The research design used was a Pre-Experimental Design in the form of a One-Shot Case Study. The population in this study were all students of class VII MTsN Sabang consisting of 4 classes with class VII3 samples collected by 25 students. The research sample was selected by purposive sampling. Data collection was carried out using a written test of 10-question questions. Data were analyzed using a formula that was calculated based on scores obtained from essay tests. The results showed the victory over the assessment of critical indicators obtained a simple assessment of getting a percentage of 76%, indicators of building skills gained 64.8%, indicators were obtained obtaining a percentage of  71.8%, indicators giving explanations received obtaining a percentage of 70.6%, and 71% of strategies. Critical learning about students in the ecosystem material through the implementation of the Discovery Learning learning model in MTsN Sabang is in the high category.